2016
DOI: 10.1016/j.molcel.2016.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Activation of Ubiquitin-Specific Proteases by β-Propeller Proteins UAF1 and WDR20

Abstract: SUMMARY Ubiquitin-specific proteases (USPs) constitute the largest family of deubiquitinating enzymes, whose catalytic competency is often modulated by their binding partners through unknown mechanisms. Here we report a series of crystallographic and biochemical analyses of an evolutionarily conserved deubiquitinase, USP12, which is activated by two β-propeller proteins, UAF1 and WDR20. Our structures reveal that UAF1 and WDR20 interact with USP12 at two distinct sites far away from its catalytic center. Witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(105 citation statements)
references
References 48 publications
(68 reference statements)
2
96
0
2
Order By: Relevance
“…During revision of this manuscript, a structure for the USP12/UAF1/WDR20 complex was published (Li et al, 2016). In this structure WDR20 binds to a number of structural elements at the palm domain of USP12 with an affinity of 7 nM.…”
Section: Discussionmentioning
confidence: 99%
“…During revision of this manuscript, a structure for the USP12/UAF1/WDR20 complex was published (Li et al, 2016). In this structure WDR20 binds to a number of structural elements at the palm domain of USP12 with an affinity of 7 nM.…”
Section: Discussionmentioning
confidence: 99%
“…USP1 has little DUB activity on its own, but is regulated by and forms a stoichiometric complex with UAF1. UAF1 also binds and activates two other DUBs, USP12 and USP46 19 , and studies that reveal how UAF1 binds and activates USP12 and USP46 suggest that UAF1 will bind to USP1 in an analogous manner 20,21 . UAF1 acts to stabilise its USP partners and increase catalytic activity 22 , and UAF1 knockout in mice is embryonic lethal, while USP1 knockouts result in a FA-like phenotype, reflecting the additional functions of UAF1 9,23 .…”
Section: Introductionmentioning
confidence: 99%
“…WDR-48, WDR-20 and USP-46 form a complex in vitro (24,28,29,36), and recently, the crystal structures of mammalian WDR-48/USP-46, WDR-48/USP-12 and WDR-48/WDR-20/USP-12 were recently solved (33)(34)(35). C. elegans USP-46 is the sole homolog of both mammalian USP-46 and USP-12, which share 90% sequence similarity with each other (12).…”
Section: Wdr-48 Binding To Usp-46 Is Required To Stabilize the Dubmentioning
confidence: 99%
“…The mechanisms underlying the ability of the WDR proteins to activate USP-12 and USP-46 were recently revealed by their crystal structures. The crystal structures of both DUBs were solved in complex with WDR-48 (33)(34)(35), and USP-12 was additionally solved in a ternary complex with WDR-48 and WDR-20 (34). Together, these structural studies revealed that the WDR proteins interact at a site distal to the active site, suggesting an allosteric mechanism underlies the ability of the WDR proteins to stimulate catalytic activity of the DUBs.…”
mentioning
confidence: 99%
See 1 more Smart Citation